2017
DOI: 10.1177/1010428317697562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endoplasmic reticulum stress on the autophagy, apoptosis, and chemotherapy resistance of human breast cancer cells by regulating the PI3K/AKT/mTOR signaling pathway

Abstract: Nowadays, although chemotherapy is an established therapy for breast cancer, the molecular mechanisms of chemotherapy resistance in breast cancer remain poorly understood. This study aims to explore the effects of endoplasmic reticulum stress on autophagy, apoptosis, and chemotherapy resistance in human breast cancer cells by regulating PI3K/AKT/mTOR signaling pathway. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed to detect the cell viability of six human breast cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…PI3K/Akt signalling pathway is one of the major upstream cellular signals in breast cancer cells . Zhong et al found that endoplasmic reticulum stress activation could promote breast cancer cell autophagy and apoptosis and enhance chemosensitivity of MCF‐7 cells by inhibiting the PI3K/AKT/mTOR signalling pathway . In current study, we found the HO‐1 up‐regulated by p‐Akt promoted autophagy and pharmorubicin resistance.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…PI3K/Akt signalling pathway is one of the major upstream cellular signals in breast cancer cells . Zhong et al found that endoplasmic reticulum stress activation could promote breast cancer cell autophagy and apoptosis and enhance chemosensitivity of MCF‐7 cells by inhibiting the PI3K/AKT/mTOR signalling pathway . In current study, we found the HO‐1 up‐regulated by p‐Akt promoted autophagy and pharmorubicin resistance.…”
Section: Discussionsupporting
confidence: 53%
“…2 Zhong et al found that endoplasmic reticulum stress activation could promote breast cancer cell autophagy and apoptosis and enhance chemosensitivity of MCF-7 cells by inhibiting the PI3K/AKT/mTOR signalling pathway. 19 In current study, we found the HO-1 up-regulated by p-Akt promoted autophagy and pharmorubicin resistance. The result suggested that the inhibition of PI3K/Akt signalling pathway might contribute to the pharmorubicin resistance in breast cancers cells.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Autophagy can function as a cellular housekeeper by removing damaged organelles and recycling macromolecules; therefore, autophagy can protect cancer cells, particularly during malignant transformation and carcinogenesis [12]. A growing body of evidence indicates that autophagy can help human cancer cells survive by conferring apoptosis resistance, and inhibition of autophagy causes caspase-dependent apoptosis cell death, especially in the presence of other therapies [13, 14]. Understanding the interplay between apoptosis and autophagy in tumors is crucial to identify new targets for cancer therapy and improve the therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%